Hubungan Aktivitas Fisik Dengan Kejadian Diabetes Melitus Tipe 2 - Trevia, Reni; Nurul Salmi, Dwi; Salim, Daeng Ramadhan (Jurnal Amanah Kesehatan, 2024)
Diabetes Mellitus (DM) Type 2 is a global health problem that is increasing. The prevalence of diabetes continues to increase globally. In 2023, it is estimated that more than 422 million people worldwide are living with diabetes, with the majority of cases being type 2 diabetes. It is estimated to reach 1.3 billion by 2050. The cause of type 2 Diabetes Mellitus is lack of physical activity. This study aims to identify the relationship between physical activity and the incidence of type 2 Diabetes Mellitus at the Andalas Health Center, Padang City. This study uses a quantitative method with a Descriptive Analytical approach. This study was conducted from August to November 2024 using the Accidental sampling technique on 30 respondents. Data analysis in this study used univariate and bivariate analysis. The results of the study showed that there was a significant relationship between low physical activity and the incidence of Type 2 DM p-value (0.024: p <0.05), This study is expected to provide concrete recommendations for efforts to prevent and treat type 2 diabetes, as well as increase public awareness of the importance of a healthy lifestyle in reducing the risk of this disease. Keywords: Diabetes Mellitus type 2; Physical activity